2006
DOI: 10.1590/s1519-38292006000300005
|View full text |Cite
|
Sign up to set email alerts
|

Total serum vitamin C concentration in pregnant women: implications for a healthy pregnancy

Abstract: OBJECTIVES: total serum vitamin C (L-ascorbic acid) concentration was measured in 90 pregnant women, 30 in each trimester (age range 18-35 years) and a control group of age-matched non-pregnant women. METHODS: total serum vitamin C concentration was measured using the 2.4-dinitrophenylhydrazine method which involves the conversion of vitamin C to dehydroascorbic acid in the presence of copper (II) ions and subsequent measurement of the resulting bis-hydrazone at 540nm. RESULTS: the total vitamin C concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
2
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
(23 reference statements)
3
3
2
6
Order By: Relevance
“…The levels of vitamin C observed in our study were similar to those reported by others [26] . Our results indicate that vitamin C may be one of the contributors to preterm delivery.…”
Section: Discussionsupporting
confidence: 92%
“…The levels of vitamin C observed in our study were similar to those reported by others [26] . Our results indicate that vitamin C may be one of the contributors to preterm delivery.…”
Section: Discussionsupporting
confidence: 92%
“…This could be true because of inability of humans to synthesis vitamin C. In the present study, no significant changes in vitamin C levels were observed in both second and third trimesters of normal and pre-eclamptic pregnancies. This is contrary to the work of Luqman et al 2008 (14) and Hassan et al 2006 (25) who observed decreasing level of vitamin C as pregnancy advances, though their sample size was small and dietary exposure may be different. However, our observation can be the result of increasing gestational age which is usually accompanied with increase tissue demand of nutrients and increase appetite.…”
Section: Discussioncontrasting
confidence: 75%
“…En línea con lo anterior, ambos grupos de gestantes mostraron concentraciones más elevadas de MDA y un índice de EOx (MDA/AA) mayor respecto del grupo control de no embarazadas (adolescentes y adultas). Al igual que otros autores (5,17,18) Ruiz-Fernández N. y col.…”
Section: Discussionunclassified